Nonlinear Analysis of Reinforced Concrete Slabs atElevated Temperature - Hadee Said, Ahmed; A. Abdul -Razzak, Ayad (Iraqi Journal of Civil Engineering, 2012)
AbstractIn this paper a nonlinear finite element analysis is presented to simulate the fire resistance of reinforced concrete slabs at elevated temperatures. An eight node layered degenerated shell element utilizing Mindlin/Reissner thick plate theory with initial stiffness technique is employed. The proposed model considered cracking, crushing, and yielding of concrete and steel at high temperatures. More complicated phenomena like concrete transient thermal strain and concrete spalling are excluded in the present analysis. The validation of the proposed model is examined against experimental data of previous researches and shows good agreement.Keywords: Fire resistance, Material nonlinearity, Reinforced Concrete Slabs